"Le pays attend de vous une attitude ferme et sans équivoque": the Belgian Judiciary and "Judicial Sabotage" 1940-1950 - Zurné, Jan Julia (Crime, histoire & sociétés, 2021)
During the German occupation of 1940-1944, the Belgian judiciary sabotaged its own investigations concerning violent attacks on collaborators in order to protect members of resistance groups. This article deals with the practice of "judicial sabotage" and shows how and why magistrates chose this strategy. Legal considerations, national identity and pragmatism were decisive factors, as well as the experience of occupation during the First World War and the specific characteristics of the occupation of Belgium in 1940-1944. This case study may serve as an example of how local institutions interact with occupying forces and use their room for manoeuvre to protect both the population and their own professional interests.